HUBUNGAN REMUNERASI DAN BUDAYA KERJA DENGAN KEPUASAN KERJA TENAGA KESEHATAN DI RUMAH SAKIT - Basuki, Hari (NATUJA: Jurnal Ekonomi Syariah, 2026)
Job satisfaction among healthcare workers constitutes a critical determinant of hospital service quality, as it is closely associated with employee performance, organizational commitment, and workforce sustainability. Remuneration and organizational culture are widely recognized as key factors influencing job satisfaction; however, empirical evidence in hospital settings remains fragmented and inconsistent. This study aims to systematically synthesize existing empirical findings regarding the relationship between remuneration, organizational culture, and job satisfaction among healthcare workers in hospitals through a Systematic Literature Review (SLR). Relevant studies were identified from Google Scholar, Garuda, and ScienceDirect using keywords related to remuneration or compensation, organizational culture, and job satisfaction. Selected articles were analyzed and synthesized using a narrative approach. The findings indicate that remuneration is significantly associated with job satisfaction, particularly when remuneration systems are perceived as fair, transparent, and performance-based. In addition, a positive organizational culture, characterized by professionalism, fairness, collaboration, and open communication, contributes to job satisfaction both directly and indirectly, primarily through motivation and organizational commitment. These results underscore the importance of aligning equitable remuneration policies with the strengthening of organizational culture to enhance healthcare workers’ job satisfaction and improve hospital service quality.